Reaksi Investor Sebelum dan Sesudah Pemilihan Presiden Republik Indonesia Tahun 2024 (Studi Kasus Perusahaan Sektor Pertambangan yang Tercatat di BEI) - Putri Wulandari; Crescentiano Agung Wicaksono (ITB AAS Indonesia, 2025)
The Presidential Election of the Republic of Indonesia is a significant political event that influences various aspects, including the economy. Political policies are one of the factors investors consider when making decisions. This study aims to examine investor reactions to the Presidential Election of the Republic of Indonesia. Investor reactions are measured using abnormal return and trading volume activity in mining sector companies listed on the Indonesia Stock Exchange (IDX), as well as the exchange rate of the rupiah. The sample was selected using purposive sampling, comprising a total of 59 companies. The study employs an event study method covering a 20-day period before and after the 2024 Presidential Election of the Republic of Indonesia, held on February 14, 2024, using the Wilcoxon signed rank test. The findings reveal significant differences in abnormal return, trading volume activity, and the rupiah exchange rate before and after the 2024 Presidential Election of the Republic of Indonesia.